Revitalization of Financial Freedom Based on Maqashid Al-Syariah Fi Hifdz Al-Mal - Ubaidillah, Ubaidillah; Nur, Iffatin; Khamami, Achmad Rizkon (Proceedings of Annual Conference for Muslim Scholars, 2024)
Current global economic instability and weak personal financial management make the economy increasingly complicated. Implementation maqashid syariah fi hifdz al-mal offers new improvisations to revitalize financial freedom. This research explores integration maqashid syariah fi hifdz al-mal in financial planning and management to improve financial well-being. Aspect hifdz al-mal not only protects assets but also strengthens the financial system and increases financial stability. This research design uses a qualitative case study approach. The findings of this study demonstrate applicability maqashid syariah fi hifdz al-mal in managing assets leads to financial freedom which is more inclusive. In addition, this approach increases public confidence in the financial system and contributes to more efficient and sustainable resource management. This research offers valuable scientific knowledge for individuals and policy makers in designing financial strategies that are more responsive and ethical and support social welfare with a sustainable economy.